2020
DOI: 10.1007/s42832-020-0070-2
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting mycorrhizal dogmas: Are mycorrhizas really functioning as they are widely believed to do?

Abstract: Since the discovery of mycorrhizas, dogmas have been developed regarding their function, ecology, and distribution. We explore if these dogmas are valid, and if there are research biases toward regions inhabited by most researchers and away from regions inhabited by most plant species. We found, first, that the mycorrhizal status is known in less than 1% of plant species, with few having proven mycorrhizal benefits for growth and development. Second, the mycorrhizal status of a plant species varies within fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 105 publications
0
39
0
1
Order By: Relevance
“…Notably, in this study, R. irregularis was more efficient at increasing P and Zn 2+ acquisition in T. grandis shoots than other mycorrhizal fungi, which could therefore enhance the yield and nutritional quality of T. grandis nuts in SAR-impacted areas. Numerous studies have confirmed the positive effects of AMF on nutrient uptake and plant quality, which can be considered as an assurance against their deterioration caused by unfavorable factors [ 23 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in this study, R. irregularis was more efficient at increasing P and Zn 2+ acquisition in T. grandis shoots than other mycorrhizal fungi, which could therefore enhance the yield and nutritional quality of T. grandis nuts in SAR-impacted areas. Numerous studies have confirmed the positive effects of AMF on nutrient uptake and plant quality, which can be considered as an assurance against their deterioration caused by unfavorable factors [ 23 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our current precepts on the function of mycorrhizas are mainly based on assumptions from experimental data of studies using limited species under certain conditions, hereby researchers are encouraged to revisit mycorrhizal dogmas, especially for their non-nutritional bene ts (Albornoz et al 2021). Therefore, ECM-associated C exudation and its effects on soil bacterial structure warrant further study.…”
Section: Introductionmentioning
confidence: 99%
“…Human activity has had substantial effects on plant N uptake through both the selection of leguminous crops which are estimated to have increased N fixation by 32-53 Tg N/year (Galloway et al, 1995) and the intensification of production systems for food and fibre by the application of about 110 Tg N/year of fertilisers in 2020/21 (IFA, 2020). While the quantity of P fertilisers applied to plants is known (about 17.5 Tg P/year), values for the uptake of P by mycorrhiza are very uncertain because although most vascular plant families can be mycorrhizal, not all species in a family are, and not all mycorrhizal roots are active in P acquisition (Albornoz et al, 2021). In soils with high P status, suppression of AMF has been widely reported so that benefits to crops given P fertiliser are typically small or absent (Ryan & Graham, 2018).…”
Section: Nutrient Acquisition For Food Productionmentioning
confidence: 99%